Cell surface mechanics gate embryonic stem cell differentiation - Bergert, M; Lembo, S; Sharma, S; Russo, L; Milovanović, D; Gretarsson, KH; Börmel, M; Neveu, PA; Hackett, JA; Petsalaki, E; Diz-Munoz, A (Cell Press, 2020)
Cell differentiation typically occurs with concomitant shape transitions to enable specialized functions. To adopt a different shape, cells need to change the mechanical properties of their surface. However, whether cell surface mechanics control the process of differentiation has been relatively unexplored. Here we show that membrane mechanics gate exit from naive pluripotency of mouse embryonic stem cells. By measuring membrane tension during early differentiation, we find that naive stem cells release their plasma membrane from the underlying actin cortex when transitioning to a primed state. By mechanically tethering the plasma membrane to the cortex by enhancing Ezrin activity or expressing a synthetic signaling-inert linker, we demonstrate that preventing this detachment forces stem cells to retain their naive pluripotent identity. We thus identify a decrease in membrane-to-cortex attachment as a new cell-intrinsic mechanism that is essential for stem cells to exit pluripotency.